Parameterizing bubble‐mediated air‐sea gas exchange and its effect on ocean ventilation. Issue 3 (30th August 2013) - Liang, Jun‐Hong; Deutsch, Curtis; McWilliams, James C.; Baschek, Burkard; Sullivan, Peter P.; Chiba, David
<x xml:space="preserve">Abstract</x> [1] Bubbles play an important role in the exchange of gases between the atmosphere and ocean, altering both the rate of exchange and the equilibrium gas saturation state. We develop a parameterization of bubble‐mediated gas fluxes for use in Earth system models. The parameterization is derived from a mechanistic model of the oceanic boundary layer that simulates turbulent flows and the size spectrum of bubbles across a range of wind speeds and is compared against other published formulations. Bubble‐induced surface supersaturation increases rapidly with wind speed and is inversely related to temperature at a given wind speed, making the effect of bubbles greatest in regions that ventilate the deep ocean. The bubble‐induced supersaturation in high‐latitude surface waters compensates a substantial fraction of the undersaturation caused by surface cooling. Using a global ocean transport model, we show that this parameterization reproduces observed saturation rate profiles of the noble gas Argon in the deep Atlantic and Pacific Oceans. The abyssal argon supersaturation caused by bubbles varies according to gas solubility, ranging from ∼0.7% for soluble gases like CO2 to ∼1.7% for less soluble gases such as N2. Bubble‐induced supersaturation may be significant for biologically active gases such as oxygen.